Reporting Mobile Device-Mediated Text to Manage Action and Agency in Co-Present Conversation - Robles, Jessica S.; DiDomenico, Stephen M.; Raclaw, Joshua; Joyce, Jack B. (Social Interaction. Video-Based Studies of Human Sociality, 2023)
The paper considers the role of agency in human interaction with mobile devices. We use multimodal conversation analysis to trace how mobile screen content is reproduced as locally relevant for updating information for co-present interlocutors. While informing-centered actions supported by mobile devices may sometimes have the character of an agentic intrusion into the local interaction, we show that the organization of device-accessed information and its meaningfulness is nonetheless positioned in relation to how device-supported updates are animated into social action by human participants. This research contributes to understanding how device-related content is sequentially incorporated into face-to-face interaction.